Prevalence of Chronic Pelvic Pain by Sexual Orientation in a Large Cohort of Young Women in the United States. Issue 6 (1st May 2022) - Tabaac, Ariella R.; Chwa, Cindy; Sutter, Megan E.; Missmer, Stacey A.; Boskey, Elizabeth R.; Austin, S. Bryn; Grimstad, Frances; Charlton, Brittany M.
ABSTRACT: Background: Sexual minority (lesbian, bisexual, mostly heterosexual) young women face many sexual and reproductive health disparities, but there is scant information on their experiences of chronic pelvic pain, including an absence of information on prevalence, treatment, and outcomes. Aim: The purpose of this study was to describe the characteristics of chronic pelvic pain experiences of young women by sexual orientation identity and gender of sexual partners. Methods: The analytical sample consisted of a nationwide sample of 6, 150 U.S. young women (mean age = 23 years) from the Growing Up Today Study who completed cross-sectional questionnaires from 1996 to 2007. Outcomes: Age-adjusted regression analyses were used to examine groups categorized by sexual orientation identity (completely heterosexual [ref.], mostly heterosexual, bisexual, lesbian) and gender of sexual partner (only men [ref.], no partners, both men, and women). We examined differences in lifetime and past-year chronic pelvic pain symptoms, diagnosis, treatment, and quality of life outcomes. Sensitivity analyses also examined the role of pelvic/gynecologic exam history and hormonal contraceptive use as potential effect modifiers. Results: Around half of all women reported ever experiencing chronic pelvic pain, among whom nearly 90% had past-year chronic pelvic pain. Compared to completely heterosexual women, there was greater risk of lifetime chronic pelvic pain among mostly heterosexual (risk ratio [RR] = 1.30, 95% confidence interval [CI]: 1.22–1.38), bisexual (RR = 1.30, 95% CI: 1.10–1.52), and lesbian (RR = 1.23, 95% CI: 1.00–1.52) young women. Additionally, compared to young women with only past male sexual partners, young women who had both men and women as past sexual partners were more likely to report chronic pelvic pain interfered with their social activities (b = 0.63, 95% CI: 0.25–1.02), work/school (b = 0.55, 95% CI: 0.17–0.93), and sex (b = 0.53, 95% CI: 0.05–1.00). Clinical Implications: Healthcare providers, medical education, and field-wide standards of care should be attentive to the way sexual orientation-based healthcare disparities can manifest into differential prognosis and quality of life outcomes for women with chronic pelvic pain (particularly bisexual women). Strengths & Limitations: Our study is the first to examine a variety of chronic pelvic pain outcomes in a nationwide U.S. sample across different outcomes (ie, past-year and lifetime). Though limited by sample homogeneity in terms of age, race, ethnicity, and gender, findings from this article provide foundational insights about chronic pelvic pain experiences of sexual minority young women. Conclusion: Our key finding is that sexual minority women were commonly affected by chronic pelvic pain, and bisexual women face pain-related quality of life disparities.